Breast cancer and aging: Standing on the shoulders of a giant. Issue 2 (March 2020) - Karuturi, Meghan S.; Sedrak, Mina S.; Magnuson, Allison; Freedman, Rachel; Jatoi, Aminah; Smith, Bejamin D.; Kimmick, Gretchen G.
Abstract: With the aging of the US population, the number of individuals age 65 or older who will be diagnosed with breast cancer is expected to rise. Despite this, older adults with breast cancer remain severely under-represented in cancer clinical trials. Numerous studies have highlighted disparites in care experienced by older patients with breast cancer. Dr. Arti Hurria was one of the most influential leaders in oncology to shed light on this vunerable and growing population. By uniting the fields of geriatrics and oncology, she brought together a powerful community of like-minded individuals and, through collaborative research, pioneered the current day approach and care of older patients with cancer. In this review, we highlight Dr. Hurria's contribution in breast oncology. Specifically, we describe her work on functional and cognitive effects of breast cancer therapy, shared-decision making, toxicity risk prediction, and breast cancer therapeutics.